(untitled) (MAUSAM, 2002)
Aridity Anomaly Index (AAI), based on Thornthwaite’s water balance technique, has been used to identify the extent and persistence of aridity anomalies over 33 sub-divisions of India during a period of 10 years from 1990 to 1999. Regional and temporal analysis has been carried out to identify the areas and periods of intense and prolonged persistence. This study has shown that 1992 was worst hit by the aridity conditions, which emerged in 5 or more fortnights. All sub-divisions of north India were affected by moderate aridity during 1990, 1992-94 and 1999. Similarly, all sub-divisions of peninsular India were influenced by moderate aridity during 1991, 1993 and 1999. Severe aridity appeared in all sub-divisions of peninsular India during 1990. The duration of severe aridity was less than that of moderate aridity during all years. Moderate and severe aridity appeared simultaneously in 5 or more fortnights in maximum 9 sub-divisions in 1992 and occurred during maximum 5 years in Madhya Maharashtra. Moderate aridity in 5 or more fortnights emerged each year during 1990 to 1999 in coastal Andhra Pradesh. In 1991, maximum 55% sub-divisions were affected by severe aridity in 9th fortnight, whereas Saurashtra & Kutch was affected in 1996 and north Interior Karnataka in 1999 during maximum 7 fortnights. In the year 1992, maximum number of sub-divisions under moderate and severe persistence was 70% and 24% respectively. In north India, moderate persistence appeared in east Rajasthan in all nine years except 1996, with its longest duration of 8 fortnights in 1995. West Madhya Pradesh, in peninsular India, was affected by moderate aridity during 7 fortnights in each year during the period of study from 1990 to 1999.